Programmable multi-channel wireless transceiver module development kit - Contento, Eden D. (2007)
The project, Programmable Multi-Channel Wireless Transceiver Module Development Kit, offers multi-channel, multi-frequency, multi-power, multi-modulation scheme and multi-data rate operations, making it flexible and easier to customize for specific applications. The transceiver can utilize the 315, 433, 868, and 915 MHz frequency bands. Data can be transmitted with an output power ranging from -30 dBm to 10 dBm, using different modulation schemes including ASK, OOK, FSK, GFSK, and MSK, at data rates from 19.2 kbps to 250 kbps. The transceiver can send data in form of packets, which incorporates error checking mechanisms thus increasing its reliability. Another important feature of the kit is its ability to operate up to four transceiver boards simultaneously. This increases the effective data rate of the system up to 1Mbps. Commercial viability was also observed to bring down the cost of the development kit compared to non-local ones. The project was developed to provide local institutions and universities with affordable and readily accessible platform for wireless development and experimentation. This development kit can be a very good training ground for university students and researchers to enhance their capabilities and become more competitive in the wireless system and applications industry, thus accelerating the development of wireless technology here in the Philippines. A user manual is provided to assist future users of the development kit.